Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevphyseducres.14.010123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the most common concept inventories in physics: What are we assessing?

Abstract: Assessing student learning is a cornerstone of educational practice. Standardized assessments have played a significant role in the development of instruction, curricula, and educational spaces in college physics. However, the use of these assessments to evaluate student learning is only productive if they continue to align with our learning goals. Recently, there have been calls to elevate the process of science ("scientific practices") to the same level of importance and emphasis as the concepts of physics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
(55 reference statements)
2
18
0
Order By: Relevance
“…for a substantial set of example 3DL assessment items, and to Underwood et al . ( 35 ) and Laverty and Caballero ( 36 ) for comparisons between traditional and 3DL assessment items]. In alignment with the intent of the Framework ( 9 ) that the three dimensions be integrated, we report the results in a binary way, that is, an assessment item either met the criteria for all three dimensions or it did not.…”
Section: Methodsmentioning
confidence: 99%
“…for a substantial set of example 3DL assessment items, and to Underwood et al . ( 35 ) and Laverty and Caballero ( 36 ) for comparisons between traditional and 3DL assessment items]. In alignment with the intent of the Framework ( 9 ) that the three dimensions be integrated, we report the results in a binary way, that is, an assessment item either met the criteria for all three dimensions or it did not.…”
Section: Methodsmentioning
confidence: 99%
“…Among the many tests developed for engineering and physics education in the United States [48][49][50][51][52][53][54][55], one is devoted to fluid mechanics [5,6]. Initiated by a cooperative effort between Jay Martin and John Mitchell at the University of Wisconsin-Madison and Ty Newell at the University of Illinois, Champaign-Urbana in 2001, it led to a final version in 2006 with the aim of promoting student understanding of fluid mechanics, as taught in mechanical engineering in the United States.…”
Section: The American Fluid Mechanics Concept Inventory (Fmci)mentioning
confidence: 99%
“…Such studies will help identify which instructional strategies are effective at improving students' modeling abilities in experimental physics contexts. 23. Do students enact revisions to the equipment, apparatus, or models?…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…In particular, there is a need to create instruments that measure students' competence with modeling. For example, Laverty and Caballero [23] showed that none of the four most widely used physics concept surveys target the concept of systems and system models or the practice of developing and using models. While there are a few ongoing efforts to assess some aspects of students' model-based reasoning in introductory physics lab and lecture courses [24][25][26], no modeling assessments exist for upper-division labs.…”
Section: Introductionmentioning
confidence: 99%